PELAKSANAAN PROGRAM PERCEPATAN PENCEGAHAN DAN PENURUNAN STUNTING DI KECAMATAN LIMA PULUH KOTA PEKANBARU TAHUN 2022 - Novriansyah, Muhammad Riki; Zebua, Ben Hansel Notatema (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Lima Puluh District is an area in Pekanbaru City, Riau Province. This district was chosen as the research object due to the discovery of 60 cases of stunting in Lima Puluh District, the highest number compared to 14 other districts, and the lack of nutrition service personnel, with only one nutrition service officer in Lima Puluh District. The study analyzed the implementation of the program to accelerate stunting prevention and reduction and its inhibiting factors using Edwards III's theory, which covers four aspects: Communication, Resources, Disposition, and Bureaucratic Structure. This study employed a qualitative-descriptive approach, with primary data consisting of interviews, documentation, and observations, and secondary data in the form of evidence, notes, or reports. The results of the study indicate that the implementation of the Stunting Prevention and Reduction Acceleration Program in Lima Puluh Kota District, Pekanbaru, in 2022 has been carried out, but is not yet perfect. First, the communication aspect tends to be ineffective due to the lack of community interest in participating in education and outreach provided by integrated health posts (Posyandu) and community health centers (Puskesmas). Second, the Resource Aspect still needs to be improved by considering incentives that can improve the quality of Posyandu cadres. Third, the Disposition Aspect, implementers have demonstrated a positive disposition through actions that are always ready, active, and responsible in carrying out each stunting prevention program. Fourth, the Bureaucratic Structure, implementers have understood and carried out their duties and authorities. Keywords: Implementation – Program – Stunting - acceleration - prevention